PARADOXES OF ARAB POLITICAL SYSTEMS CHANGES - V. A. Kusnetsov (Vestnik MGIMO-Universiteta)
This article explores the antinomies of development of different Arab political systems, drawing on the theory of social order by D. North, J. Wallis and B. Weingast. The author analyses all Arab countries as "orders of limited access", mature or fragile. This approach enables the author to follow the rationale of political development in fragile and failed states, as well as the logic of how political relations form in quasi-states, without raising the question of statehood as such. However, the level of generalization inherent in the theory of social order impedes an analysis of the diverse political reality as we encounter in the Middle East. Therefore, the author (enhances the theoretical framework), identifying three models of political transformation in the Arab world: the Levant-Iraqi, North African and Gulf-Libyan models. Each of these models is organized in its own way, not only in socio-political terms, but also has been developing according to its own logic over the past several decades. In 2010 and 2011, all Arab states were faced with the same, well-known set of challenges and threats. And though responses to these differed case by case and were predetermined by the belonging of a particular system to a particular transformational model, the result was the same: the emergence of drivers of future change, applicable to the entire region. From the author's perspective, these drivers have included: first, a kind of «future phobia», which drives the political behavior of both masses and elites; and second, economic crisis, with which most governments of the region have struggled. At first glance, the political transformations occurring as a result of these drivers appear similar. Democratic procedures, electoral processes and the role of civil society appear to have strengthened and play an increasingly prominent role. The paradox is that, in practice, the above-described regional trends can entail very different social-political consequences, presaging modernization in some places, while driving the archaization of the state in others, depending on which model the respective state belongs to. At the same time, these processes of modernization and archaization stand in a complex relationship with the processes of strengthening / weakening of "orders of limited access": while, tactically, the majority of conscious actions taken by elites is aimed at strengthening "orders of limited access", in the long run, such actions can raise risks and weaken political systems.